Implementasi Haversine Formula untuk Pembuatan SIG Jarak Terdekat ke RS Rujukan COVID-19 - Kristoko Dwi Hartomo; Hanna Prillysca Chernovita; Chandra Husada (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Haversine formula-based GIS has been created to find closest location to referral hospital handling COVID-19 in Semarang City. The objectives of this study were (1) to determine closest distance and compare the results with the calculation of Find Nearest Tool and Google Maps and (2) to design GIS. It was done through (i) primary and secondary data creation and processing, (ii) accuracy measurement using Haversine formula. GIS is built after the calculation results are obtained. Calculation of the distance from user’s starting point to referral hospital can be generated using Haversine formula. Comparison of measurement results between Haversine formula-based GIS and Find Nearest Tool, the average differences is 13 meters, the smallest difference is 3 meters and the largest difference is 40 meters. The differences between the calculation results of Haversine formula and Google Maps, the smallest difference is 0 meters, the largest difference is 5 meters, and the average differences is 3 meters. GIS creation obtained through designing use case, activity, class diagram, and user interface. The conclusion is Haversine formula-based GIS can be used as